Respuesta :

Answer:

Step-by-step explanation:

We could multiply the first equation by -3 and, separately, multiply the second equation by 4.  The result would be:

-12x - 15y = -21

12x  - 8y = -48

the x terms now cancel.  The result is:

- 15y = -21

- 8y = -48

----------------

-23y = -69, or y = 3.  If y = 3, then 3x - 2y = -12 becomes:

3x - 2(3) = -12, or

3x - 6 = -12, or    3x = -6, and so x = -2.

The solution is (-2, 3).

Answer:

In the slot for 4x + 5y = 7 is -3. Which makes -21.

In the slot for 3x-2y=-12 is 4. Which makes -48.

Step-by-step explanation:

When you add the -21 and -48 you get -69.

The solution is (-2, 3)

Hope this helped : )

If it did, please remember to like and give stars?

ACCESS MORE